Kontroversi Nasikh-Mansukh dalam Al-Qur’an - Qosim Nurseha Dzulhadi (Universitas Darussalam Gontor, 2009)
A theory on naskh which develops grantedly in the Islamic sciences, naturally raises a controversy, which indicates that this concept is arguable and discussable. On the other hand, contemporary muslim scholars have solved significantly on this controversy. This article tries to present some problems of naskh in relation with the Holy Al-Qur’an. Among the problems discussed in this regard is a controversy on the meaning of naskh, particularly in the development of Interpretation of Quranic verses in relation to the development of Islamic jurisprudence. The view of muslim scholars and their argumentation to approve the nasikh-mansukh in the Al-Qur’an is also another point to be presented which argued by the view of contemporary Muslim scholars who criticize this concept. Finally, it is concluded that a theory on naskh is contemporary issue which is exaggerated and developed not on the basis of an adequate scientific criticism, therefore, muslim ummah should consider this problem as a logical consequence of the topic (al-tah ayyuz al-mawdhû‘iy).